Quantification of gentle pull using pinch-pull gripping system based on fugl meyer and manual muscle test protocols for rehabilitation - Alsayed, Abdallah S. Z. (2020)
Fugl Meyer Assessment (FMA) and Manual Muscle Test (MMT) protocols are widely used in post-stroke rehabilitation assessment. In the protocol related to pinch function evaluation, the patients are required to pinch a pincer object and the therapists would apply some resistance equivalent to 4/5 score of MMT to distinguish between subjects whom is fully recovered and yet to recover. The resistance applied by the therapist using 4/5 MMT is also described as applying gentle pull in FMA protocol. Subject’s ability or inability to pinch and resist the gentle pull would lead to either score 1 (not recovered) or score 2 (recovered). However, the gentle pull (4/5 MMT) is subjective which may result in intra-rater and inter-rater variations. In this study, the gentle pull is determined quantitatively using a developed pinch-pull gripping system. The pinch-pull gripping system consists of a customized pinch force load cell measuring the pinch force, pulling force load cell measuring the pulling force, linear actuator applying the automatic pull, and displacement sensor to track the pinch slip. In determining the quantitative value of gentle pull, four therapists were recruited at Universiti Putra Malaysia Teaching Hospital and instructed to pinch a pincer object and exert a gentle pull equivalent to 4/5 MMT as they would apply in clinical practice. The results showed that the quantitative value of the therapist’s gentle pull is 6.59±0.94 N. In order to investigate if this gentle pull force is able to distinguish the normal volunteers, fifty normal volunteers representing score 2 were recruited and their pulling forces were measured and compared with the quantitative value of the gentle pull. The volunteers were instructed to pinch the pincer object and resist the automatic pull of the linear actuator as much as possible before the pincer object slips away from their fingers. The results show that the normal volunteers exerted mean pulling forces at slip away of 14.84±3.57 N and 13±2.72 N for right and left hands, respectively. This indicates that the normal volunteers attributed to score 2 is able to resist the gentle pull exerted by the therapist. Furthermore, the amount of gentle pull applied by the therapists is indeed suitable and that the pinch-pull gripping system is able to measure the pulling force accurately. The results also show that despite the volunteers exhibiting a small slip displacement, they could still resist the increase in the pulling force up to slip away. Thus, the presence of slip displacement prior to slip away is inadequate to judge the subject’s ability to resist the gentle pull. In rehabilitation, the pinch-pull gripping system can be used to evaluate the recovery of pinch function. In order to achieve a full recovery, the patient should be able to pinch the pincer object and resist the 6.59 N pull exerted by the pinchpull gripping system.